A meta-analytic review of the effect of guilt on compliance. (2nd January 2016) - Boster, Franklin J.; Cruz, Shannon; Manata, Brian; DeAngelis, Briana N.; Zhuang, Jie
Abstract: Meta-analytic procedures were used to estimate the effect of experienced guilt on compliance. Examination of 47 effect sizes indicated that inducing guilt is an effective means by which to increase compliance, ρ  = .26. Moreover, despite coding for numerous substantive and methodological moderators, there was no evidence of moderation in these data. Instead, correcting for measurement error in the independent variable and restriction in range in the dependent explained all variance in effect sizes, yielding a corrected effect size of ρ ′ = .35.